4-{[(4Z)-5-Oxo-2-phenyl-4,5-dihydro-1,3-oxazol-4-ylidene]methyl}phen yl acetate - Baldaniya, B.B.; Jotani, M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title molecule, C(18)H(13)NO(4), shows a dihedral angle between the terminal acetyl group (r.m.s. deviation = 0.0081 angstrom) and remaining non-H atoms (r.m.s. = 0.0734 angstrom) of 53.45 (7)degrees. The configuration about the central olefinic bond is Z and overall the molecule has a U-shaped conformation. Supramolecular chains along the b-axis direction are found in the crystal structure. These are stabilized by (C=O)center dot center dot center dot pi (ring centroid of the 1,3-oxazole ring) interactions [3.370 (2) angstrom].